2021
DOI: 10.3390/ijerph182010905
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behaviors, Mental Health, and Risk Perceptions during the Beginning of the COVID-19 Pandemic among Mexican Adult Smokers

Abstract: Mexico is one of the countries most affected by COVID-19. Studies have found that smoking behaviors have been impacted by the pandemic as well; however, results have varied across studies, and it remains unclear what is causing the changes. This study of an open cohort of smokers recruited from a consumer panel (n = 2753) examined changes in cigarettes per day (CPD), daily vs. non-daily smoking, recent quit attempts, perceived stress, depression, and perceived severity of COVID-19 at two points during the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…There were 10 articles excluded due to their study methodology, not being related to the main objective, not having enough data or because they were reviews. After a meticulous review of each article, 15 studies met the inclusion criteria [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 10 articles excluded due to their study methodology, not being related to the main objective, not having enough data or because they were reviews. After a meticulous review of each article, 15 studies met the inclusion criteria [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, many factors were associated with higher levels of anxiety during the COVID-19 pandemic in Mexico, such as being female [ 13 , 16 , 19 , 22 , 23 ], younger age [ 16 , 22 ], history of direct or indirect contact with a COVID-19 confirmed case [ 16 , 23 ] and the presence of specific physical symptoms [ 16 ]. However, in some studies, no differences between genders or age concerning anxiety were identified [ 14 , 17 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations